2021
DOI: 10.1038/s41467-021-22471-y
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptotic cell death triggered by conjugated linolenic acids is mediated by ACSL1

Abstract: Ferroptosis is associated with lipid hydroperoxides generated by the oxidation of polyunsaturated acyl chains. Lipid hydroperoxides are reduced by glutathione peroxidase 4 (GPX4) and GPX4 inhibitors induce ferroptosis. However, the therapeutic potential of triggering ferroptosis in cancer cells with polyunsaturated fatty acids is unknown. Here, we identify conjugated linoleates including α-eleostearic acid (αESA) as ferroptosis inducers. αESA does not alter GPX4 activity but is incorporated into cellular lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
107
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(119 citation statements)
references
References 82 publications
11
107
1
Order By: Relevance
“…As indicated by our results as well as by other in vitro and in vivo studies [ 1 , 49 ], CLnAs are phytochemicals with promising anti-cancer effects that could be exploited as preventive or even therapeutic agents. CLnAs are mainly found in seed oils of specific plants and the CLnA content can reach up to 80% of the total lipids [ 5 ], making CLnAs accessible nutritional phytochemicals.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…As indicated by our results as well as by other in vitro and in vivo studies [ 1 , 49 ], CLnAs are phytochemicals with promising anti-cancer effects that could be exploited as preventive or even therapeutic agents. CLnAs are mainly found in seed oils of specific plants and the CLnA content can reach up to 80% of the total lipids [ 5 ], making CLnAs accessible nutritional phytochemicals.…”
Section: Discussionsupporting
confidence: 76%
“…Since ferroptosis relies on an extensive accumulation of PUFA-derived lipid peroxides [ 32 , 33 ], we assumed that PunA may trigger ferroptosis in carcinoma cells. Although some previous reports indicated that CLnAs are likely to trigger apoptosis [ 7 , 23 , 60 ], ferroptosis has recently appeared as a potent cell death pathway underlying CLnA cytotoxicity on cancer cells [ 49 ]. In the present study, we evaluated the impact of two ferroptosis inhibitors, namely ferrostatin-1 (fer-1) and α-tocopherol (α-T), on the cytotoxicity of PunA on HCT-116 and FaDu carcinoma cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations